The idea of Silence Right in Period of Contractual Negotiation Study in the Anglo-American legal system - عبد الرضا حسين عبد الله; حسوني محمد عويز (Journal of Legal Sciences, 2019)
The period of negotiations is essential in the formation of contracts especially economic importance, but the legal value varies from legal system to another, where the freedom of negotiation is absolute in the Anglo-American system, which leaves its impact on the duty of the flags regarding the principle of good faith in the stage of negotiations nodal. The Anglo-American legal system recognizes the rule of the right to remain silent. The buyer’s responsibility at the negotiation stage is that it rejects the principle of good faith at this stage, and then attempts to achieve justice through other mechanisms surrounding the principle. A number of exceptions are broadly decided to the degree Can be said to be working to achieve the same objectives of the principle.